Organizational readiness for the digital transformation: a case study research - Sanchez, Marisa A; Zuntini, Juana I (Revista Gestão & Tecnologia, 2018)
The aim of this research work is to formulate a framework that explains resources, capabilities and management choices necessary to respond to the new environment. The research methodology is based on literature review and an in-depth case study based on three enterprises. The framework describes (a) the impact of digital innovations on external forces; (b) adequate strategies arising from a value chain analysis; (c) resources and capabilities of critical importance. The article contributes to the state of management literature by describing how small and medium size companies respond to the digital transformation process.